Suicidalidade em pacientes com transtorno de pânico e agorafogia: prevalência e fatores associados - Bauer, Victor Augusto [UNESP] (2014)
Introduction: Psychiatric disorders are the main risk factors for suicidal behaviors or 'suicidality', but there are few studies on this issue involving patients with anxiety disorders in general and panic disorder (PD) in particular. Most PD patients that seek treatment have agoraphobia associated to the disorder (PAD). Investigations of suicidality among PAD patients have been largely inconclusive and there are no Brazilian publications on this issue. Objectives: this study aimed to estimate the prevalence of various lifetime suicidal behaviors (feeling that life is not worth living, wishing to be dead, suicidal thoughts, plans and attempts) in PAD patients and to evaluate sociodemographic and clinical factors associated with these behaviors. Method: A cross-sectional study was conducted with a sample of adult patients presenting PAD (DSM-IV criteria) undergoing treatment in a private clinic in Bauru and in the outpatient service for anxiety and obsessive-compulsive disorders at Botucatu Medical School - São Paulo State University from January 2011 to October 2013. The assessment instruments used were: a questionnaire designed to collect sociodemographic and clinical data, the Panic and Agoraphobia Scale (PAS) to evaluate PAD clinical severity and the Mini International Neuropsychiatric Interview (M.I.N.I.) to evaluate the co-occurrence of other psychiatric disorders. Initially, the prevalence of the outcomes of interest (suicidal behaviors) was calculated; then, bivariate analyses were performed between these outcomes and several demographic and clinical variables. For the categorical explanatory variables the Chi-squared and the Fisher exact tests were used, whereas for the quantitative variables (e.g.: age, schooling years, PAS score) the Student t test (normal distribution) and the Mann-Whitney test (non-normal distribution) were used. Results: 45 patients (66.7% women and 33.3% men) were assessed. Ages ranged from 19 to 68; ...